2012
DOI: 10.15809/irriga.2012v17n4p494
|View full text |Cite
|
Sign up to set email alerts
|

DESENVOLVIMENTO INICIAL DE PLANTAS DE Eucalyptus platyphylla SUBMETIDAS A NÍVEIS DE SALINIDADE

Abstract: RESUMOO objetivo deste trabalho foi avaliar o comportamento morfológico de plantas de Eucalyptus platyphylla quando submetidas a cinco níveis de salinidade de solo. A pesquisa em questão foi conduzida em casa de vegetação, na área experimental do Departamento de Engenharia Rural da FCA/UNESP, Botucatu-SP, utilizando-se de vasos plásticos preenchidos com solo contendo doses de NaCl, em quantidades suficientes para elevar o nível de condutividade elétrica. O experimento foi realizado em blocos ao acaso, em esque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…The increase in electrical conductivity of the irrigation water and consequent reduced potential of the solution were not sufficient to generate significant alterations to growth variables (height, diameter and biomass). The results confirm those of Lopes et al (2012) when evaluating the growth of eucalyptus irrigated with saline water. The sustained growth under the conditions imposed represents an important sign of tolerance to salinity (Matos et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in electrical conductivity of the irrigation water and consequent reduced potential of the solution were not sufficient to generate significant alterations to growth variables (height, diameter and biomass). The results confirm those of Lopes et al (2012) when evaluating the growth of eucalyptus irrigated with saline water. The sustained growth under the conditions imposed represents an important sign of tolerance to salinity (Matos et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…According to Lopes et al (2012), the Eucalyptus platyphylla plants are tolerant to irrigation water salinity, as they present small variation in diameter and plant height when irrigated with low quality water. However, little is known about the tolerance of Eucalyptus plants to salinity.…”
Section: Introductionmentioning
confidence: 99%
“…S. tuberosa, but the frequency of reservoirs with low quality water should be taken into consideration when setting up the orchard. Irrigation with saline water is the reality in semiarid regions where quality water is not available for agriculture (Lopes, Lima, & Klar, 2012). Salinity causes drop in crop yields due to the osmotic, toxic and/or nutritional effects (Negrão Schmöckel, & Tester, 2017;Zörb, Geilfus, & Dietz, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil has about 30 million hectares with irrigation potential spread from north to south (BRASIL, 2015). The saline water irrigation is a reality in semi-arid regions that do not have quality water for agriculture (LOPES et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, conductivity lower than 4 dS m -1 may not have an adverse effect on the tree productivity. Souza et al (2015) and Lopes et al (2012), evaluated seedlings of Eucalyptus urophylla and Eucalyptus platyphylla and concluded that the growth of eucalyptus plants has little variation when the plants are irrigated with water conductivity from 0 to 8 dS m -1 , but, most of the surveys were carried out with Eucalyptus plants, requiring the development of studies with other forest species such as Tectona grandis.…”
Section: Introductionmentioning
confidence: 99%